The time of your life: time congruence and its relations to authenticity and mindfulness - Ascencio, Jaime, author; Rickard, Kathryn, advisor; Byrne, Zinta, committee member; Wdowik, Melissa, committee member (Colorado State University. Libraries, 2017)
Integrity has been proposed as a new way of conceptualizing time use by examining the ways a person's actual time use reflects the individual's values and preferences. Evidence from previous studies shows numerous benefits from experiencing congruence between actual and ideal time use. In this study, I examined authenticity and mindfulness as potential precursors to integrity, and perceived choices as a potential control variable. Correlations were confirmed between the three variables. Due to the incorrect completion of the daily diary by the majority of participants, I was unable to create a diary-based measure of integrity. However, a single-item measure of integrity was included, which was used for time-related analyses. It was found that mindfulness, authenticity, and perceived choice had positive correlations with integrity, but that mindfulness accounted for these correlations when they were entered into a model together. These results suggest that mindfulness could be further researched as an intervention to improve people's levels of integrity. Key suggestions for improving the daily diary entries include using daily reminders, reformatting the entry template, and implementing a training day for participants before they complete the entries.
Keywords: integrity; perceived choice; time use; mindfulness; authenticity; time congruence